Basic Biology and Applications of Actinobacteria - Enany, Shymaa (IntechOpen, 2018)
Actinobacteria have an extensive bioactive secondary metabolism and produce a huge amount of naturally derived antibiotics, as well as many anticancer, anthelmintic, and antifungal compounds. These bacteria are of major importance for biotechnology, medicine, and agriculture. In this book, we present the experience of worldwide specialists in the field of Actinobacteria, exploring their current knowledge and future prospects.